Plasmodium berghei NK65 in Combination with IFN-γ Induces Endothelial Glucocorticoid Resistance via Sustained Activation of p38 and JNK - Zielińska, Karolina A.; de Cauwer, Lode; Knoops, Sofie; Van der Molen, Kristof; Sneyers, Alexander; Thommis, Jonathan; De Souza, J. Brian; Opdenakker, Ghislain; De Bosscher, Karolien; Van den Steen, Philippe E. (Frontiers in Immunology, 2017)
Malaria-associated acute respiratory distress syndrome (MA-ARDS) is an often lethal complication of malaria. Currently, no adequate therapy for this syndrome exists. Although glucocorticoids (GCs) have been used to improve clinical outcome of ARDS, their therapeutic benefits remain unclear. We previously developed a mouse model of MA-ARDS, in which dexamethasone treatment revealed GC resistance. In the present study, we investigated GC sensitivity of mouse microvascular lung endothelial cells stimulated with interferon-γ (IFN-γ) and Plasmodium berghei NK65 (PbNK65). Upon challenge with IFN-γ alone, dexamethasone inhibited the expression of CCL5 (RANTES) by 90% and both CCL2 (MCP-1) and CXCL10 (IP-10) by 50%. Accordingly, whole transcriptome analysis revealed that dexamethasone differentially affected several gene clusters and in particular inhibited a large cluster of IFN-γ-induced genes, including chemokines. In contrast, combined stimulation with IFN-γ and PbNK65 extract impaired inhibitory actions of GCs on chemokine release, without affecting the capacity of the GC receptor to accumulate in the nucleus. Subsequently, we investigated the effects of GCs on two signaling pathways activated by IFN-γ. Dexamethasone left phosphorylation and protein levels of signal transducer and activator of transcription 1 (STAT1) unhampered. In contrast, dexamethasone inhibited the IFN-γ-induced activation of two mitogen-activated protein kinases (MAPK), JNK, and p38. However, PbNK65 extract abolished the inhibitory effects of GCs on MAPK signaling, inducing GC resistance. These data provide novel insights into the mechanisms of GC actions in endothelial cells and show how malaria may impair the beneficial effects of GCs.